ANALISIS PENERAPAN SISTEM PENGENDALIAN INTERN PENJUALAN KREDIT PADA PT. NUSANTARA SURYA SAKTI BENGKULU - Fitria, Indah (Program Studi Agribisnis Faperta Universitas Muhammadiyah Bengkulu, 2021)
ABSCTARCT This internal control system is run to provide reasonable assurance about the achievement of objectives that is, reliability of financial reporting, compliance with applicable laws and regulations, effectiveness and efficiency of operations. Therefore it is necessary to evaluate the internal control system to the sale to maintain the survival of the company and the achievement of corporate objectives The purpose of this study Knowing to know how the implementation of internal control system of credit sales at PT. Nusantara Surya Sakti Bengkulu and whether the system of internal control system of credit sales at PT. Nusantara Surya Sakti Bengkulu has fulfilled the Internal Control System based on generally accepted accounting principles (PABU)This study uses a type of comparative analysis research. This method is a presentation of data derived from the problems faced by the company, from the problems that are analyzed by using an approach based on existing theories then compare with what is realized in the object of researchThe results of research network designation procedures that form the credit sales system at PT. Nusantara Surya Sakti Bengkulu is sales order procedure, delivery procedure, billing procedure, account receipt procedure, and sales distribution procedure. In the procedure that forms the credit sales system at PT. Nusantara Surya Sakti Bengkulu is running well. Keywords: Implementation, internal control system, credit sales